THE MIDWIFERY CARE ON NEONATE IN GAMPONG BAYU, INGIN JAYA, THE DISTRICT OF ACEH BESAR - Putri, Afifa; Yusnaini, Yusnaini; Sabrida, Oktalia (Journal of Midwifery and Community Health (JMCH), 2024)
According to the Aceh Health Profile 2020, the Infant Mortality Rate (IMR) refers to the number of infants who die during the period from birth until the infant has not yet reached the age of 1 year per 1,000 live births. The Infant Mortality Rate in Aceh by the end of 2020 reached 10/1000 live births.  This occurred due to the insufficient maternal and child health services that meet the standards, the lack of capacity improvement for midwives in villages in managing newborns, and the lack of understanding among mothers in the early detection of fetal danger signs.  This case report aims to provide normal midwifery care for a neonate in Gampong Bayu, Ingin Jaya, The district of Aceh Besar, and document it in the midwifery care format (SOAP). The first care was conducted on May 13, 2022, after data collection showed that the mother reported her baby was the first child born 3 hours earlier at the midwifery clinic on May 13, 2022, at 17:20, with full-term gestational age and the baby in a healthy condition. Physical examination results were normal, and care was provided to the mother regarding the recommendations for Early Initiation of Breastfeeding (IMD) for the newborn, administration of Vitamin K injection, HBO injection after 1 hour of birth, explaining to the mother how to keep the baby warm, breastfeeding properly, umbilical cord care, and maintaining cleanliness.